Geomagnetic paleointensity dating of mid-ocean ridge basalts from the neo-volcanic zone of the Central Indian Ridge - Yutaka Yoshimura; Masakazu Fujii (Earth, Planets and Space, 2024)
Abstract Describing the evolution of the neo-volcanic zone in the spreading ridge is essential for understanding the dynamics and environments of abyssal basins. However, the absolute dating of ocean floor basalts is generally difficult. As a characteristic age indicator, absolute intensity of past geomagnetic field (absolute paleointensity, API) is useful to date ocean floor basalts. In this study, we adopted the Tsunakawa–Shaw method to measure APIs of whole-rock seafloor basalts collected from a conical cone on the Central Indian Ridge and performed rock magnetic experiments. We conducted the experiments on a total of 18 specimens (two or three specimens from each of eight lava sites). Six specimens from two lava sites with different morphologies (pillow and sheet), three for each, passed the acceptance criteria. API means at site level are 33.0 ± 1.0 and 35.8 ± 1.7 μT, respectively. The similarity of API site means suggests that they erupted within a short period. These site-level API means are approximately 0.7 to 0.8 times the present geomagnetic intensity of 46.0 μT at the sampling sites. The accepted specimens show higher Curie temperature, lower initial intensity of natural remanent magnetization, higher ratio of saturation remanence to saturation magnetization (Mrs/Ms), and signal of harder magnetic mineral than rejected ones. Our primary comparison between the two site-level API means and the 1590–present high-resolution IGRF-13 + gufm1 model constrains that the eruption timing of the conical cone to be < 1590 CE. When we compared the two site-level API means with the paleointensity curves calculated from the BIGMUDI4k.1 and ArchKalmag14 k.r, we found that they overlap in the period of − 7575 to −1675 CE or − 25 to 1590 CE, which may be the eruption timing of the conical cone. We concluded that timing of recent volcanic eruption in abyssal environment could be investigated by using appropriate rock magnetic selection and carefully examined API. Graphical Abstract